Interactive Analog Layout Editing with Instant Placement and Routing Legalization - Gao, Xiaohan; Zhang, Haoyi; Liu, Mingjie; Shen, Linxiao; Pan, David Z.; Lin, Yibo; Runsheng WANG; Ru HUANG (IEEE Transactions on Computer-Aided Design of Integrated Circuits and Systems, 2022)
Analog layout design is still primarily reliant on manual efforts. Current fully automated workflows are unable to meet the expectations for flexible customization and are incompatible with existing manual workflows. For both performance and productivity, interactive layout editing has the ability to bridge the gap between manual and automated flows. We present an interactive layout editing system in this study that includes well-defined commands for both placement and routing customization. This is a pioneering work that provides a holistic study on the interactive design methodology for analog layouts and its capability of speeding up design closure. Our framework comes up with instant placement legalization and routing adjustment mechanism for rapid layout update and modification. The framework is capable of handling realtime user interaction and improving the performance of fully automated layout generators verified by post-layout simulation on real-world analog designs. Experimental results demonstrate the performance enhancement on real-world analog designs with only a few editing commands. As examples, on the low-dropout regulator, our framework can reduce the overshot down and up voltage to nearly 1=3 of layout generated by automation tool with two editing commands, and on the operational transconductance amplifier, it achieves 33:5% better common mode rejection ratio with only one command.